1994
DOI: 10.1002/gea.3340090303
|View full text |Cite
|
Sign up to set email alerts
|

Platforms in the akalche at E1 Mirador, Peten, Guatemala and their implications

Abstract: Late Preclassic Period platforms were surveyed and test-excavated in a seasonal swamp or akalche, at the large ancient lowland Maya site of El Mirador in Peten, Guatemala. Pedological, hydrological, and archaeological evidence suggest that the climatic and hydrological regimes were drier than they are today to permit habitation and warrant the investment in labor. Nevertheless, observations of present conditions, including the clayey soils, indicate that the akalche was almost as inhospitable in antiquity as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Harrison (1977) revived the "bajos as lakes" hypothesis based on the presence of large complexes of wetland fields detected via aerial photography in several bajos in southern Quintana Roo, Mexico. A model of the bajos as breadbaskets within the central Maya heartland soon arose (Adams et al, 1981), but Pope and Dahlin (1989) argued that the southern Quintana Roo bajos were hydrologically anomalous and that conditions within most elevated, interior bajos were not conducive to wetland agriculture e a conclusion based in part on field work by Dahlin and soil scientist John Foss in the El Mirador Bajo, Guatemala (Dahlin et al, 1980;Dahlin and Dahlin, 1994).…”
Section: Wetter Bajos and Maya-induced Desiccationmentioning
confidence: 97%
“…Harrison (1977) revived the "bajos as lakes" hypothesis based on the presence of large complexes of wetland fields detected via aerial photography in several bajos in southern Quintana Roo, Mexico. A model of the bajos as breadbaskets within the central Maya heartland soon arose (Adams et al, 1981), but Pope and Dahlin (1989) argued that the southern Quintana Roo bajos were hydrologically anomalous and that conditions within most elevated, interior bajos were not conducive to wetland agriculture e a conclusion based in part on field work by Dahlin and soil scientist John Foss in the El Mirador Bajo, Guatemala (Dahlin et al, 1980;Dahlin and Dahlin, 1994).…”
Section: Wetter Bajos and Maya-induced Desiccationmentioning
confidence: 97%
“…Hard-water error can result from the dissolution of ancient limestone in the watershed and incorporation of the 14 C-deficient carbon into shell carbonate (Islebe et al 1996). Dahlin and colleagues made more extensive soil investigations in a large bajo adjacent to the large center of El Mirador (Dahlin, Foss, and Chambers 1980;Pope and Dahlin 1989;Dahlin and Dahlin 1994). They found Vertisols to be the most prevalent soil within the bajo, interpreted to indicate that similar environmental conditions had prevailed throughout Maya times.…”
Section: Bajos and Wetlands In The Maya Lowlands: Earlier Researchmentioning
confidence: 99%
“…Nevertheless, it is critical to note that the seasonal swamps found today in interior bajos are far from environmentally homogeneous, with some areas having greater agricultural potential than others (Culbert et al 1996;Kunen et al 2000). Others have argued that the Vertisols prevalent today in many interior bajos would have made significant agriculture difficult Dahlin 1989, 1993;Dahlin and Dahlin 1994). They argue that these soils are often deficient in phosphorus, potassium, and zinc, low in organic matter, poorly aerated, overly acidic, subject to seasonal shrinking and swelling capable of tearing crop roots, extremely hard when dry, and plastic and sticky when wet.…”
Section: Bajos and Wetlands In The Maya Lowlands: Earlier Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…This idea was not further tested until 1959 when two side-by-side soil pits were dug in another bajo in the vicinity of Tikal, and the results suggested that this bajo had never contained a lake (Cowgill and Hutchinson, 1963). Over the next 35 years, more investigations were carried out in bajos, chiefly adjacent to archaeological sites under excavation, leading to conflicting interpretations, some of which suggested that bajos were considerably wetter environments in the past and/or more suitable to agriculture and others which seemed to refute that idea (Harrison, 1977;Dahlin et al, 1980;Gliessman et al, 1983;Culbert et al, 1990;Dahlin and Dahlin, 1994;Jacob, 1995).…”
Section: Emergence Of Geoarchaeologymentioning
confidence: 95%